Annexin V‐Modified Platelet‐Biomimetic Nanomedicine for Targeted Therapy of Acute Ischemic Stroke. Issue 16 (30th June 2022) - Quan, Xingping; Han, Yan; Lu, Pengde; Ding, Yuanfu; Wang, Qingfu; Li, Yiyang; Wei, Jianwen; Huang, Qiaoxian; Wang, Ruibing; Zhao, Yonghua
Abstract: Thromboembolic stroke is typically characterized by the activation of platelets, resulting in thrombus in the cerebral vascular system, leading to high morbidity and mortality globally. Intravenous thrombolysis by tissue plasminogen activator (tPA) administration within 4.5 h from the onset of symptoms is providing a standard therapeutic strategy for ischemic stroke, but this reagent simultaneously shows potential serious adverse effects, e.g., hemorrhagic transformation. Herein, a novel delivery platform based on Annexin V and platelet membrane is developed for tPA (APLT‐PA) to enhance targeting efficiency, therapeutic effects, and reduce the risk of intracerebral hemorrhage in acute ischemic stroke. After preparation by extrusion of platelet membrane and subsequent insertion of Annexin V to liposomes, APLT‐PA exhibits a high targeting efficiency to activated platelet in vitro and thrombosis site in vivo, due to the binding to phosphatidylserine (PS) and activated platelet membrane proteins. One dose of APLT‐PA leads to obvious thrombolysis and significant improvement of neurological function within 7 days in mice with photochemically induced acute ischemic stroke. This study provides a novel, safe platelet‐biomimetic nanomedicine for precise thrombolytic treatment of acute ischemic stroke, and offers new theories for the design and exploitation of cell‐mimetic nanomedicine for diverse biomedical applications. Abstract : An Annexin V‐modified platelet‐biomimetic nanomedicine is prepared by inserting Annexin V into the surface of platelet membrane fused tissue plasminogen activator (tPA)‐loaded liposomes for targeted therapy of acute ischemic stroke. Annexin V and platelet membrane lead to a high targeting efficiency to the stroke tissue and rapid thrombolysis via the antiplatelet activation of Annexin V and fibrinolysis by tPA.